The Bright Future of Democracy is in Education - Gregory T. Papanikos (Athens Institute for Education and Research, 2022)
Does democracy have a bright future? This brief paper addresses this question and argues, that, thanks to Prometheus, political "animals" can build a better-managed corral for their common living which includes a better provision of education for all "animals." A historical analysis of the long past may be used to discern what lies ahead. Democracy requires education and virtue, or to put it in one word, it requires pedagogy. The higher the level of pedagogy, the closer a politeia would come to an ideal democracy. Sometimes democracy is confused with equality in everything. Political "animals" are not equal, and political systems which treat people with different abilities equally have no future. An ideal society should discriminate according to levels of education obtained and the acquisition of material wealth. If the politeia is ideal, then each citizen has the same opportunity to become more educated and wealthier. In this free competition of being educated and the acquisition of individually made material wealth, ideal societies can flourish as Hesiod postulated in the 8th Century BCE and become stable despite Polybius' predictions in the 2nd-1st Century BCE of the inevitable historical cyclicality of political systems.